Managing chronic pathologies with a stepped mHealth-based approach in clinical psychology and medicine - Castelnuovo, Gianluca; Zoppis, Italo; Santoro, Eugenio; Ceccarini, Martina; Pietrabissa, Giada; Manzoni, Gian Mauro; Corti, Stefania; Borrello, Maria; Giusti, Emanuele Maria; Cattivelli, Roberto; Melesi, Anna; Mauri, Giancarlo; et al. (Frontiers in Psychology, 2015)
Chronic diseases and conditions typically require long-term monitoring and treatment protocols both in traditional settings and in out-patient frameworks. The economic burden of chronic conditions is a key challenge and new and mobile technologies could offer good solutions. mHealth could be considered an evolution of ehealth and could be defined as the practice of medicine and public health supported by mobile communication devices. mHealth approach could overcome limitations linked with the traditional, restricted and highly expensive in-patient treatment of many chronic pathologies. Possible applications include stepped mHealth approach, where patients can be monitored and treated in their everyday contexts. Unfortunately, many barriers for the spread of mHealth are still present. Due the significant impact of psychosocial factors on disease evolution, psychotherapies have to be included into the chronic disease protocols. Existing psychological theories of health behavior change have to be adapted to the new technological contexts and requirements. In conclusion, clinical psychology and medicine have to face the "chronic care management" challenge in both traditional and mHealth settings.